Aspects of prostacyclin in experimental hypertension - Botha, Julia Hilary (Rhodes University, Faculty of Pharmacy, Pharmacy, 1983)
A new prostaglandin - prostaglandin X (later renamed prostacyclin or prostaglandin I₂ (PGI₂)), was discovered by Moncada, Gryglewski, Bunting and Vane in 1976. This unstable substance was shown to be produced by vascular tissue and to be a vasodilator and the most potent endogenous inhibitor of platelet aggregation known. Because of its properties, it appeared that a lack of it may be related to the development and or maintenance of hypertension, a disorder featuring vasoconstriction and an increased tendency to arterial thrombosis. The present studies aimed to investigate this possibility using a rat model. A bioassay for prostacyclin was first perfected. This consisted of a modification of the method used by Moncada, Higgs and Vane (1977): PGI₂ released by rat aortic strips, during incubation in tris buffer, was measured by assessing the ability of the incubate to inhibit adenosine diphosphate induced aggregation of human platelets, as compared to the inhibitory effect of standard prostacyclin sodium salt. The specificity of the assay for the detection of PGI₂ was tested. The abil ity of hypertensive rat aorta to release prostacycl in was investigated in two studies. The first compared aortas of Wistar rats of the New Zealand genetically hypertensive strain (GH) with those of matched normotensive Wistar controls. In the second study, hypertension was induced by wrappi ng the ri ght kidney with surgical silk and removing the contralateral kidney. Ten weeks later, aortic generation of prostacyclin by these animals was compared with that of matched sham controls which had received identical surgical manipulation but for the application of silk to the right kidney. Contrary to expectation, in both forms of hypertension, aortas of the rats with elevated pressure produced consistently more prostacyclin than those of matched controls. In order to discover more about the relationship between elevated pressure and elevated PGI₂ production, the effect of pressure reduction with hypotensive agents on the ability of GH rat aortas to produce prostacyclin, was investigated. After pressure had been controlled within normal range for one week (achieved by oral administration of furosemide, dihydralazine and reserpine for one month), aortic PGI₂ was reduced in comparison with matched GH controls. However, the reduction was not consistent and statistical significance was not reached. Because it was subsequently reported by other workers, that some of the hypotensive agents which had been employed may effect prostaglandin levels per se, no conclusions could be drawn from this study as to any possible direct relationships between pressure and aortic prostacyclin generating capacity. A further means of reducing elevated pressure (which had no inherent effect on prostaglandin levels) was thus sought. A mechanical method was eventually selected, application of a silver clip to the aortas of GH rats, just below the diaphragm, producing an immediate reduction in pressure distal to the constriction. Eighteen hours with later, PGI₂ production by these distal aortas those of matched sham GH controls and was was compared found to be consistently reduced. These results indicate that the ability to produce PGI₂ may be influenced by prior local pressure changes and that the increased capacity of hypertensive rat aortas to generate prostacyclin may be related to the increased mechanical transmural stress consequent on elevated pressure. Since haemostatic balance must be influenced not only by vascular PGI₂ generation but also by platelet sensitivity to PGI₂, the response of GH platelets to the anti-aggregatory effect of prostacyc1in was also investigated. As it had been shown by Sinzinger, Si1berbauer, Horsch and Gall (1981) that intra-arterial infusion of PGI₂ in humans decreased platelet sensitivity to the substance, the possibility existed that platelet sensitivity in hypertension might be reduced. This hypothesis was, however, invalidated as the sensitivity of GH platelets to the anti-aggregatory effect of PGI₂ was almost identical to that of normotensive controls. The shortcomings of the methodology and the possible importance of these findings in the hypertensive animal are discussed. The idea that elevated PGI₂ in hypertension may play a protective role both with respect to platelet aggregation and in attenuating further pressure rises is considered. It is finally suggested that it will be possible to draw more accurate conclusions as to the meaning of the increased PGI₂ generation in hypertension (both in relation to vascular tone and platelet function) only when details of production of, and sensitivity to, thromboxane A₂ are known. Thromboxane A₂ (TXA₂) is a vasoconstrictor and promotor of aggregation (Hamberg, Svensson and Samuelson, 1975) and it may be that, despite elevated vascular PGI₂ generation, the TXA₂/PGI₂ balance is still tipped in favour of vasoconstriction and platelet aggregation in hypertension.
Keywords: Prostacyclin; Prostaglandins; Prostaglandin endoperoxides; Thromboxanes; Hypertension